Exploring pathways to late Holocene increased surface wetness in subarctic peatlands of eastern Canada. Issue 1 (17th May 2018) - van Bellen, Simon; Garneau, Michelle; Baird, Andy; Bourgault, Marc-André; Quillet, Anne
Abstract: The poor fens of the Laforge region, northeastern Canada, have developed under subarctic conditions. They are characterized by a microtopography of large pools and low, narrow strings. Paleorecords suggest some of these systems were once ombrotrophic and relatively dry. Taking account of their current bioclimatic position, we aimed to explore the possible pathways towards the current wet state, a process referred to as "aqualysis". We combined paleoecological methods applied to a peat core with conceptual modelling to identify factors that might plausibly explain aqualysis. Reconstructions showed the Abeille peatland became minerotrophic with high water tables between 2400 and 2100 cal yr BP. Conceptual modelling, supported by simulations using the numerical DigiBog model, allowed us to identify the effects of cooling and increased precipitation on productivity, decay, peat hydraulic conductivity and vertical peat accumulation. Both cooling and increased precipitation were required for aqualysis to occur and for wet surface conditions to persist to the present day. Increased recharge from the catchment, which also restricted drainage from the peatland center laterally, was likely critical for the development of minerotrophic conditions. The scenario of cooling and wetting in these peatlands is supported by available paleoclimate records for eastern Canada.